Effects of tannic acid supplementation on growth performance, gut health, and meat production and quality of broiler chickens raised in floor pens for 42 days - Choi, Janghan; Liu, Guanchen; Goo, Doyun; Wang, Jinquan; Bowker, Brain; Zhuang, Hong; Kim, Woo Kyun (Frontiers in Physiology, 2022)
A study was conducted to investigate the effects of tannic acid (TA) supplementation on growth performance, gut health, antioxidant capacity, gut microbiota, and meat yield and quality in broilers raised for 42 days. A total of 700 one-day-old male broiler chickens (Cobb500) were allocated into 5 treatments with 7 replicates of 20 birds per pen. There were five treatments: 1) tannic acid 0 (TA0: basal diet without TA); 2) tannic acid 0.25 (TA0.25: basal diet+0.25 g/kg TA); 3) tannic acid 0.5 (TA0.5: basal diet+0.5 g/kg TA); 4) tannic acid 1 (TA1: basal diet+1 g/kg TA); and 5) tannic acid 2 (TA2: basal diet+2 g/kg TA). The dietary phases included starter (D 0 to 18; crumble feed), grower (D 18 to 28; pellet feed), and finisher (D 28 to 42; pellet feed). On D 18, the supplementation of TA linearly reduced body weight (BW) and average daily feed intake (ADFI) (P<0.05), and on D 28, the supplementation of TA linearly reduced BW, average daily gain (ADG), and feed conversion ratio (FCR) (P<0.05). Relative mRNA expression of genes related to mucin production (MUC2), tight junction proteins (CLDN2 and JAM2), and nutrient transporters (B0AT1 and SGLT1) was linearly increased by the supplementation of TA (P<0.05). The supplementation of TA tended to linearly increase the relative abundance of the family Enterobacteriaceae (P=0.08) and quadratically increased the relative abundance of the families Lachnospiraceae and Ruminococcaceae in the cecal microbial communities (P<0.05). On D 36, the ratio of the phyla Firmicutes and Bacteroidetes was quadratically reduced by the supplementation of TA (P<0.05). On D 42, bone mineral density and the lean to fat ratio were linearly decreased by the supplementation of TA (P<0.05). On D 43, total chilled carcass weight was linearly reduced (P<0.05), and proportion of leg weight was increased by supplementation of TA (P<0.05). The supplementation of TA linearly reduced pH of the breast meat (P<0.05) and linearly increased redness (a*) (P<0.05). Although the supplementation of TA positively influenced gut health and gut microbiota in the starter/grower phases, it negatively affected overall growth performance, bone health, and meat production in broilers on D 42.